Stubble Burning: A Challenging Issue in Punjab - Sonali Sharma; Anju Bala (Revista Electronica de Veterinaria, 2024)
Beautiful hills are the main attraction point of North India. Not only of citizens of India also the visitors from foreign countries come there to enjoy snowy hills but stubble burning is curse for this beauty of north India. Environment Protection Act 1986, The Air (Prevention and Control of Pollution) Act, The water (Prevention and Control of Pollution) Act are established to provide safety to environment and the living and non-living species of environment. But farmers violate the established laws and act and they burns the stubbles and agriculture waste which cause many health issues as well as harms environment. The main aim of this study is to enlighten the causes, problems and suggestions to avoid and control stubble burning.